Identification of a novel HLA‐C*04 allele, HLA‐C*04:162. Issue 3 (17th January 2014) - Wang, D.; Gao, S.; Xu, Y.; He, L.; Zhen, J.; Zou, H.
Abstract HLA‐C*04:162 differs from the closely matching allele C*04:01:01:01 by one nucleotide substitution in exon 4 at position 883 A/G.